Kajian Bahaya Bencana Banjir dengan Metode Topographic Wetness Index di Kabupaten Serang - Firman Prawiradisastra (Agency for the Assessment and Application of Technology / Badan Pengkajian dan Penerapan Teknologi (BPPT), 2018)
Coping flood hazard risk needs to be done early on. One way of handling floods from the beginning is to predict flood-prone areas with topographic wetness index method. Serang regency is a fairly frequent area of flooding therefore it is necessary to conduct a study to predict flood-prone areas. The total area of flood-prone areas in Serang Regency is 62,608 Ha based on TWI saga modeling results. The area is dominated by high and low class with 25,050 Ha and 29,741 Ha respectively. While for the middle class of 7,817 ha.